Systematic Literature Review: The Role of Education in Reducing Economic Inequality and Poverty - Muhammad Roestam Afandi; Siswanto; Najeem Olawale Adelakun (Sinergi International Journal of Education, 2026)
Education is widely recognized as a key driver of economic development and social mobility. However, disparities in access and quality of education remain significant challenges in many developing countries, including Indonesia, which may limit its potential to reduce poverty and economic inequality. This study aims to systematically examine the role of education in reducing poverty and economic inequality using a Systematic Literature Review (SLR) approach. The review analyzed 19 empirical studies published between 2017 and 2025 obtained from Garuda, Neliti, Google Scholar, and Sinta databases using the PRISMA procedure. The findings show that education consistently contributes to poverty reduction by improving human capital, expanding employment opportunities, and strengthening social mobility. However, its impact on reducing economic inequality is more conditional and depends on equitable access, quality of education, and supportive public policies. The novelty of this study lies in integrating empirical evidence that simultaneously analyzes education as a mechanism influencing both poverty reduction and inequality mitigation, while identifying contextual factors that shape this relationship in developing countries. These results highlight that inclusive and equitable education policies are essential for achieving sustainable and inclusive economic development.